Etika Bisnis dan Corporate Social Responsibility (CSR) dalam Peningkatan Reputasi dan Keberlanjutan Perusahaan di Indonesia - Caroline; Jesslyn Tiovanny; Jocelyn Marchella; Felix Thantio Yangderson; Susan Grace V Nainggolan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explain the concepts of business ethics and corporate social responsibility, analyze their interrelationship in corporate practices in Indonesia, and identify the benefits, challenges, and strategies for their implementation. The study uses a qualitative descriptive method through a literature review with content analysis to organize the data into main themes. The results show that business ethics form the basis of corporate behavior, while corporate social responsibility is a form of concrete action that supports the welfare of society and the environment. The application of both has been proven to increase public trust, reputation, and business sustainability, despite facing obstacles in the form of cultural differences, regulations, and resource requirements. This study emphasizes the importance of consistent implementation so that companies can provide positive value to society while maintaining long-term sustainability.